Effectiveness of Using Fun Easy Learn Applications in Arabic Vocabulary Mastering at Madrasah Tsanawiyah Negeri Batu - Abdul Wahab; Amaliah Farhan; Najih Syahrul Ichwan; Danial Hilmi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to describe the effectiveness of using a mobile learning-based Fun Easy Learn application on mastery of arabic vocabulary at Madrasah Tsanawiyah Negeri Batu. The Fun Easy Learn application is an educational game application to learn several languages, in this case Arabic. Learning a language by playing will certainly make it easier for students to understand the material, and students will not feel that they are learning. This application can be an alternative for educators in delivering material for their students with easy difficulty levels. This research is included in quantitative research and quasi-experimental research used is one group time series design, namely research that only uses one class, namely the experimental class. The population in this study were students of class VII I. and the number of samples in this study was 30 people. Data collection techniques with tests in the form of multiple choice questions. And the method of data collection was carried out using a pretest and posttest twice according to the given theme. This is done so that researchers can find out whether there are differences in students' mastery of understanding before and after being given treatment. While the data analysis technique in this study was carried out by using the t-test using the SPSS 26 application.